Anxiolytic-like effect of ethanolic extract of Argemone mexicana and its alkaloids in Wistar rats - Aideé Itzel Arcos-Martínez; Omar David Muñoz-Muñiz; Miguel Ángel Domínguez-Ortiz; Margarita Virginia Saavedra-Vélez; Maribel Maribel Vázquez-Hernández; Maria Gabriela Alcantara-Lopez (Mashhad University of Medical Sciences, 2016)
Objective: Argemone mexicana is a Papaveracea plant; some reports have shown their antibacterial, anti-cancer, sedative and probably anti-anxiety properties. From their aerial parts, flavonoids and alkaloids have been isolated, which are intrinsically related to some actions on the central nervous system. The aim of this study was to evaluate the anxiolytic-like effects of the plant, using its ethanolic extract and alkaloid-enriched extract obtained from fresh leaves. Material and Methods: Phytochemical screening was carried out together with evaluation of antioxidant capacity and the enrichment of alkaloids present in the extract. Subsequently, 100 and 200 mg/kg doses of ethanolic extract and alkaloid-enriched extract (200 µg/kg) were intraperitoneally administered to female Wistar rats, which were exposed to elevated plus maze (EPM) test. Picrotoxin (1 mg/kg), a non-competitive gamma-aminobutyric acid A (GABAA) chloride channel antagonist, was used in experimental procedures to evaluate if this receptor is involved in the anxiolytic-like effects of A. mexicana. To discard motor effects associated with the treatments, the rats were evaluated by the locomotor activity test. Results: Only the ethanolic extract at 200 mg/kg and alkaloid-enriched extract (200 µg/kg) produced anxiolytic-like effects similarly to diazepam 2 mg/kg on EPM test, without affecting locomotor activity. Meanwhile, the administration of picrotoxin blocked anti-anxiety effect of alkaloid-enriched extract of the plant. Conclusion: These results showed that A. mexicana is a potential anxiolytic agent and we suggest that this effect is mediated by the GABAA receptor. These effects are related to the presence of alkaloids.